2008
DOI: 10.1534/genetics.108.090274
|View full text |Cite
|
Sign up to set email alerts
|

A “FLP-Out” System for Controlled Gene Expression in Caenorhabditis elegans

Abstract: We present a two-part system for conditional FLP-out of FRT-flanked sequences in Caenorhabditis elegans to control gene activity in a spatially and/or temporally regulated manner. Using reporters, we assess the system for efficacy and demonstrate its use as a cell lineage marking tool. In addition, we construct and test a dominant-negative form of hlh-12, a gene that encodes a basic helix-loop-helix (bHLH) transcription factor required for proper distal tip cell (DTC) migration. We show that this allele can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 48 publications
1
78
0
Order By: Relevance
“…We have shown that ZF1-tagged proteins can be degraded in all examined embryonic and larval somatic cell types, and by altering the promoter used to express ZIF-1, we have demonstrated both spatial (tissue-specific promoter) and temporal (heat-shock promoter) control of targeted protein destruction. By combining ZF1 tagging with existing conditional gene expression technologies, such as the FLP-FRT system and tissue-specific heat-shock methods Voutev and Hubbard, 2008;Bacaj and Shaham, 2007;Churgin et al, 2013), it should be feasible to achieve simultaneous spatial and temporal control of gene product function. Using recently developed genome editing techniques, we have shown that sequences encoding the ZF1 tag can be inserted directly into endogenous loci, greatly facilitating genetic analysis by ZF1-tagging and obviating the need for a loss-of-function mutation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that ZF1-tagged proteins can be degraded in all examined embryonic and larval somatic cell types, and by altering the promoter used to express ZIF-1, we have demonstrated both spatial (tissue-specific promoter) and temporal (heat-shock promoter) control of targeted protein destruction. By combining ZF1 tagging with existing conditional gene expression technologies, such as the FLP-FRT system and tissue-specific heat-shock methods Voutev and Hubbard, 2008;Bacaj and Shaham, 2007;Churgin et al, 2013), it should be feasible to achieve simultaneous spatial and temporal control of gene product function. Using recently developed genome editing techniques, we have shown that sequences encoding the ZF1 tag can be inserted directly into endogenous loci, greatly facilitating genetic analysis by ZF1-tagging and obviating the need for a loss-of-function mutation.…”
Section: Discussionmentioning
confidence: 99%
“…rex-32 was excised from animals containing both FRT sites, using FLP recombinase, which was introduced into the gonad by injecting FLP-encoding RNA at concentration of 1500 ng/ml. RNA was made by in vitro transcription from a PCR fragment containing the T7 promoter, the FLP recombinase sequence, derived from pGC92 (Voutev and Hubbard 2008), and 59-and 39-UTRs appropriate for germline translation of C. elegans mRNAs: 59-UTR, ATT TAG GTG ACA CTATAG AAT ACA CGG AAT TCT AGA TGA TCC CCG CGT ACC GAG CT CAGA AAAA; 39-UTR, GCC TGA GCT CAC GTC GAC CGG GGC CCT GAG ATC TGC TGC AG.…”
Section: Flp/frt Experimentsmentioning
confidence: 99%
“…ctbp-1a::V5 was amplified from the resulting plasmid pMSCVpuro ctbp-1a::V5 with primers containing attachment sites attB4 and attB3. This amplicon was incorporated into the pGC188 (Jane Hubbard: Addgene plasmid 19619) (Voutev and Hubbard, 2008) plasmid in a BP reaction using the Gateway® Cloning system (Life Technologies, Australia). For expression in the nervous system, the panneuronal promoter of the aex-3 gene (1333 bp) was amplified from N2 genomic DNA and inserted into pENTR™/D-TOPO® plasmid (Life Technologies) according to the manufacturer's instructions.…”
Section: Generating a Transgenic Strain For Expression Of Ctbp-1a In mentioning
confidence: 99%
“…For expression in the nervous system, the panneuronal promoter of the aex-3 gene (1333 bp) was amplified from N2 genomic DNA and inserted into pENTR™/D-TOPO® plasmid (Life Technologies) according to the manufacturer's instructions. A LR reaction was performed with the following plasmids: pENTR p aex-3, pGC188 ctbp-1a::V5 and the destination plasmid, pGC247 (Jane Hubbard: Addgene plasmid 19634) (Voutev and Hubbard, 2008). For constitutive expression of ctbp-1a::V5, the gfp sequence was flipped out of the plasmid pAER10 p aex-3::FRT-gfp-FRT::ctbp-1a::V5 following co-transformation with the pMS40 plasmid (Snaith et al, 1996) in BL21(DE3) cells (Invitrogen) and IPTG (isopropyl-beta-D-thiogalactopyranoside) induction of FLP recombinase.~8 μg of the resulting plasmid pAER2 p aex-3::ctbp-1a::V5 which also contains the unc-119(+) sequence in the backbone was linearised by digestion with EcoRV for biolistic transformation into unc-119(ed3) mutants.…”
Section: Generating a Transgenic Strain For Expression Of Ctbp-1a In mentioning
confidence: 99%